The Cross-Cultural Conditions of Trust - Rob B. McClary (Adult Education Research Conference, 2015)
An important aspect of being an effective educator is gaining the trust of one’s students. Nowhere is this more critical, and more challenging, than for our military leaders whose jobs require them to teach and train the service members of our allies and coalition partners. Participants in this roundtable will be invited to share their experiences of building cross-cultural trust in their classrooms, and to engage in a learning activity that explores how they view the behaviors that lead to trust.